* ‘Det her skal alle da opleve’: Racial transformation som erkendelsesproces og mangfoldighedsværktøj i dansk anti-racistisk performance - Danbolt, Mathias; Myong, Lene (Peripeti, 2018)
The article analyzes the self-declared anti-racist performance project Med Andre Øjne (MAØ) [Through Different Eyes], which since 2011 has served as a sought-after diversity tool in Denmark. The purpose of MAØ is, through the use of racial and gendered transformations, to allow participants to ‘put themselves in the other’s place’ in order to produce empathy and compassion. Through a critical analysis of MAØ’s invitation to embody and appropriate the experience of racialized minorities in order to engage questions of everyday racism, the article highlights the limits of empathy as an anti-racist methodology, while arguing that MAØ reproduces a depoliticized understanding of racism that reduces anti-racism to individualized self-transformation.